2018
DOI: 10.1021/acs.jafc.8b00775
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Promotes Slow Myosin Heavy Chain Expression via Akirin2 and the AMP-Activated Protein Kinase Signaling Pathway in Porcine Skeletal Muscle Satellite Cells

Abstract: This study aimed to investigate the effect of arginine on the expression of slow myosin heavy chain (MyHC) I and its underlying mechanism in porcine skeletal muscle satellite cells. Our results showed that arginine upregulated the mRNA (1.54 ± 0.08; p < 0.01) and protein (2.01 ± 0.01; p < 0.001) levels of MyHC I. We also showed that arginine upregulated the expression of Akirin2 (1.35 ± 0.1; p < 0.05) and increased the NO content (1.56 ± 0.04; p < 0.001). Akirin2 siRNA abolished arginine-induced upregulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(54 reference statements)
3
14
0
Order By: Relevance
“…Thus, we build the in vitro cell culture model that additional amino acids (Met, Leu, or Lys) adding into the culture medium at the selected concentrations (0.6 mM) can significantly promote milk synthesis and activation of the mTOR signaling. The in vitro cell culture models in some literatures are similar to ours (Chen et al, ; Dong et al, ; Guo et al, ; Li et al, ).…”
Section: Discussionsupporting
confidence: 74%
“…Thus, we build the in vitro cell culture model that additional amino acids (Met, Leu, or Lys) adding into the culture medium at the selected concentrations (0.6 mM) can significantly promote milk synthesis and activation of the mTOR signaling. The in vitro cell culture models in some literatures are similar to ours (Chen et al, ; Dong et al, ; Guo et al, ; Li et al, ).…”
Section: Discussionsupporting
confidence: 74%
“…It was previously shown that NO contributes to slow MyHC transcription by AMPK activation in myotubes (Chen et al, 2018b), so we suggested that NO content restoration during rat hindlimb unloading would activate AMPK in rat soleus muscles. However, according to the results of our experiment L-arginine administration did not lead to AMPK activation.…”
Section: Discussionmentioning
confidence: 69%
“…The isolation and identification of porcine skeletal muscle satellite cells were performed as described in our previous study (13) . Porcine skeletal muscle satellite cells were grown in Dulbecco's modified Eagle's medium/F12 supplemented with 15 % fetal bovine serum and with 100 U/ml penicillin and 100 μg/ml streptomycin at 37°C in a 5 % CO 2 atmosphere.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…Previous studies have suggested that Arg plays multiple physiological functions in animals, such as antioxidant activity, reproductive performance and fat deposition (8)(9)(10)(11) . A few recent studies have shown that Arg promotes more type I muscle fibres formation in mice and MyHC I expression in porcine skeletal muscle satellite cells (12)(13)(14) . However, no information has been reported about the effect of Arg on type I muscle fibre type formation in weaning piglets.…”
mentioning
confidence: 99%